2019
DOI: 10.26417/ejed.v2i3.p41-46
|View full text |Cite
|
Sign up to set email alerts
|

The Blockchain Challenge for Higher Education Institutions

Abstract: Blockchain technology is argued to be the next “big” digital technology trend that will challenge a number of organizations, including higher education institutions. In contrast, higher education institutions have a history of being slow to adopt new digital technologies in the organizational apparatus. The question that remains discussing is whether universities will approach blockchain technologies in ways that are different from traditional research and education. This paper intends to discuss three particu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 5 publications
0
27
0
Order By: Relevance
“…In line with the new keywords that are associated with this area of research, it is necessary to point out "blockchain university" [142]. This gives the blockchain the ability to facilitate the operation of educational platforms where students securely manage the data and content they share [143]. That is, this technology allows the transfer of digital assets without any intermediary, and some currents guess that it will have an impact similar to that of the Internet [144,145].…”
Section: Keyword Analysismentioning
confidence: 99%
“…In line with the new keywords that are associated with this area of research, it is necessary to point out "blockchain university" [142]. This gives the blockchain the ability to facilitate the operation of educational platforms where students securely manage the data and content they share [143]. That is, this technology allows the transfer of digital assets without any intermediary, and some currents guess that it will have an impact similar to that of the Internet [144,145].…”
Section: Keyword Analysismentioning
confidence: 99%
“…Blockchain is also applied to other financial sectors, the health, IoT, government, and education sectors. Halvdan Haugsbakken et al discuss the potential value of blockchain technology in higher education and identifies areas where the technology can increase speed, efficiency, and transparency (Haugsbakken and Langseth, 2019). Furthermore, according to (Abbasi et al, 2021), the blockchain concept has demonstrated the potential of current educational opportunities.…”
Section: Blockchain Educationmentioning
confidence: 99%
“…Although there are many issues related to the implementation of blockchain technology. General aspects that will have to be considered are: (1) the environmental cost, the amount of electricity that is needed to run complex code across many computers; (2) the time aspect, as blockchains grow, they might be slow and cumbersome; (3) the trust aspect, as it will take time for end users to make the trust leap and trust the technology, and (4) the legal aspect -the slow regulation of the value-based transfer of value over the Internet by the use of blockchain networks invites fraud [35,36]. Furthermore, another concern to be considered is unsuitability of traditional Software Development Life Cycle (SDLC) models [37] for blockchain enabled smart contract-based applications.…”
Section: Relating Workmentioning
confidence: 99%